2018
DOI: 10.1007/s00702-018-1892-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interaction of monoamine oxidase A in relation to antisocial behaviour: current and future directions

Abstract: Since the pioneering finding of Caspi and co-workers in 2002 that exposure to childhood maltreatment predicted later antisocial behaviour (ASB) in male carriers of the low-activity MAOA-uVNTR allele, frequent replication studies have been published. Two meta-analyses, one in 2006 and the other in 2014, confirmed the original findings by Caspi and co-workers. In the present paper, we review the literature, note some methodological aspects of candidate gene–environment interaction (cG×E) studies and suggest some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 160 publications
(324 reference statements)
1
35
0
1
Order By: Relevance
“…Therefore, these results would agree with Byrd et al (2019) who found that high MAO-A activity genotype would be related to aggressive behaviors and other disorders through an indirect pathway with emotional reactivity as an intermediary instead of through a direct pathway. Thus, we can speculate that neuroticism regulated by MAOA might be a common factor between the different phenotypes observed in women who had the high MAO-A activity genotype as proposed by Nilsson et al (2018).…”
Section: Mao-a Aggression and Impulsivitymentioning
confidence: 80%
See 2 more Smart Citations
“…Therefore, these results would agree with Byrd et al (2019) who found that high MAO-A activity genotype would be related to aggressive behaviors and other disorders through an indirect pathway with emotional reactivity as an intermediary instead of through a direct pathway. Thus, we can speculate that neuroticism regulated by MAOA might be a common factor between the different phenotypes observed in women who had the high MAO-A activity genotype as proposed by Nilsson et al (2018).…”
Section: Mao-a Aggression and Impulsivitymentioning
confidence: 80%
“…MAOA has been related to other mental health problems in addition to antisocial behaviors. Recent studies have suggested that could exist a common factor for all these phenotypes, and that could be emotion regulation (Nilsson, Åslund, Comasco, & Oreland, ). Then, women with high MAO‐A activity genotype who had experienced childhood maltreatment would present higher levels of emotional reactivity that could predict some pathologies, with the reverse pattern in males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current study only includes young healthy young males with no known history of traumatic experiences, which are often discussed in the context of MAOA VNTR effects. Previous findings suggest that environmental adversities might influence the effect of the MAOA VNTR on aggression (Byrd and Manuck, 2014;Nilsson et al, 2018). Future studies might therefore additionally assess stressful life-events.…”
Section: Limitationsmentioning
confidence: 99%
“…[24] ‹nsan agresif davranıının ilk G¥E (genetik ¥ çevre) çalıması 2002 yılında [25] bildirilmi ve çocuklukta kötü muameleye maruz kalmanın MAOA-L alelinin erkek taıyıcılarında daha sonra antisosyal davranıa (ASB) yol açtı¤ı gösterilmitir. [26] Mevcut çalıma için önemli olan MAO-A'nın amigdala ve OFC morfolojisini etkileyebilece¤idir. Monoamin oksidaz A geni düük (MAOA-L) veya yüksek (MAOA-H) transkripsiyon verimi ile ilikili varyantlar veren 30 baz çifti de¤iken nükleotid tandem tekrar (VNTR) polimorfizmi içerir.…”
Section: Ps‹kopat‹unclassified